High-titred neutralizing antibodies to human enterovirus 71 preferentially bind to the N-terminal portion of the capsid protein VP1 - Tan, Cheng Siang; Cardosa, Mary Jane (Springer-Verlag, 2007)
Human enterovirus 71 has emerged as an important pathogen of children in the Asia Pacific region, and it may be important to consider the development of a vaccine against this virus. Human cord serum was used as a source of neutralizing antibodies to determine whether the N- or C-terminal half of the VP1 capsid protein was more likely to harbour neutralizing determinants. Cord sera from 205 individuals were tested for neutralizing antibodies against human enterovirus 71 in an indirect ELISA against recombinant VP1 antigen as well as the N- and C-terminal portions of VP1 antigen. High-titred human neutralizing antibodies were significantly more reactive with the N-terminal half of VP1 than weak or negative sera. The N-terminal half of human enterovirus 71 is likely to have important neutralizing antibody determinants and should be investigated further in vaccine development efforts.